Re-thinking global and local manufacturing of medical products after COVID-19 - Germán Velásquez (South Centre, 2020)
The unprecedented global health crisis caused by the coronavirus (COVID-19) pandemic since the first quarter of 2020 has reopened the now-urgent discussion about the role of local pharmaceutical production in addressing the health needs in developing countries. The COVID-19 crisis has highlighted the interdependencies in the global production of pharmaceuticals—no country is self-sufficient. Many industrialized countries are making the decision to repatriate or initiate the production of active pharmaceutical ingredients (APIs) and medicines. Governments are beginning to talk about `pharmaceutical sovereignty' or `health security'. If this becomes a reality and the production of pharmaceuticals is led by nationalistic policies, developing countries that still lack manufacturing capacity will have to start or expand the local production of pharmaceuticals, whether at the national or regional level. The war to get access to the future vaccine for COVID-19 does not look easy with these new developments.
Keywords: 300; Access to COVID-19 Tools (Accelerator) - (ACT); Access to Medicines; Biologics; Coronavirus; COVAX Facility; COVID-19; Diagnostics; Global Health; Global Preparedness; Health; Health Security; Innovation; Intellectual Property; Pandemic; Pharmaceutical Sovereignty; Public Health; Research and Development (R&D); Tech Access Partnership (TAP); United Nations (UN); United Nations Conference on Trade and Development (UNCTAD); United Nations Development Programme (UNDP); United Nations Industrial Development Organization (UNIDO); Vaccine Nationalism; Vaccines; WHO; World Health Organization (WHO)